Refined tastes : sugar, confectionery, and consumers in nineteenth-century America - Woloson, Wendy A., 1964- (Johns Hopkins University studies in historical and political science ;, 2002)
"American consumers today regard sugar as a mundane and sometimes even troublesome substance linked to hyperactivity in children and other health concerns. Yet two hundred years ago American consumers treasured sugar as a rare commodity and consumed it only in small amounts. In Refined Tastes: Sugar, Confectionery, and Consumers in Nineteenth-Century America, Wendy A. Woloson demonstrates how the cultural role of sugar changed from being a precious luxury good to a ubiquitous necessity. Sugar became a social marker that established and reinforced class and gender differences."--Jacket